PARTISIPASI POLITIK SAPMA PEMUDA PANCASILA DALAM PEMILIHAN GUBERNUR JAWA TENGAH 2020 - Samuel Tuah Pinto Sagala; Puji - Astuti (Journal of Politic and Government Studies, 2020)
Local Leaders Election or District Head Election is one of the Democracy Feastas a form of people's sovereignty to choose the leaders in an area. The Central JavaProvince in 2018 held the Election of Governor and Deputy Governor as the largestform of political feast in Central Java. The election of the Governor of Central Java in2018 was attended by various groups both from parties and organizations in society.Sapma Pemuda Pancasila is one of the organizations that developed in the communityand participated in Central Java Governor Elections 2018. The level and form ofpolitical participation of the Sapma Pemuda Pancasila organization is interesting toresearch because Sapma Pemuda Pancasila is an organization consisting of youngpeople who are the future successors of the nation specifically in the 2018 Central JavaGovernor election. This study uses a mixed method research to combine descriptivequalitative and quantitative descriptive data with use Huntington and Nelson politicalparticipation theory.The results of this research describe various forms of political participation ofthe Sapma Pemuda Pancasila organization in Central Java Governor Election 2018according to Huntington and Nelson political participation theory. The conclusion ofthis research shows that the level of political participation of Sapma Pemuda Pancasilais quite high, it can be influenced by both internal and external factors.